Qualifications of the Ideal Tourism School Administrator: A RepGrid Review - Yasemin Yetkin; Fatih Kancınar; Halil İbrahim Özok (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)

(untitled)
The school administrator has one of the most important roles in the success of an institution and in the execution of processes, especially in some fields like tourism including practical parts. For this success and effective management, there are certain qualities that the school administrator should have. The aim of this study is to examine the cognitive constructs of teachers and to reveal the qualities that the administrator working in tourism should have. Repertory Grid Technique was used in the study, which was prepared according to qualitative research patterns. The study group consisted of 40 teachers working in tourism schools, who worked with at least 6 different administrators. As a result of the study, honesty (η=8, 20.0%), (2) fairness (η=6, 15.0%), (3) personal feature; emotional intelligence; sensitivity (η=5, 12.5%) are the most important qualifications. When these results are taken into consideration, it becomes clear that ideal school administrators should pay attention to these qualifications. It is an important suggestion to pay attention to these qualities in the selection of tourism school administrators.